Don't you forget about me : a Gossip Girl novel - Von Ziegesar, Cecily (New York : Little, Brown, 2007)
The Gossip Girl and her friends spend a summer partying before heading off to college in the fall.
Keywords: High schools -- Fiction; Interpersonal relations -- Fiction; Wealth -- Fiction; Schools -- Fiction; Teenagers -- New York (State) -- New York -- Juvenile fiction; Gossip -- New York (State) -- New York -- Juvenile fiction; High school students -- New York (State) -- New York -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Juvenile fiction